Quantification of critical success factors of contractors in Cambodia: AHP approach - Durdyev, Serdar; Eng, Hai Theng; Cheng, Kam Yuen (Journal of Management, Economics, and Industrial Organization, 2018)
Project success is commonly defined as a completion of a construction project within stipulated time, estimated cost and required quality. Undoubtedly, contractor’s, who is one of the influencing stakeholders for project activities, performance is critical for successful project completion. Thus, being the first work in its kind, this study evaluates the CSFs for contractors in Cambodia. The AHP approach was adopted for pairwise comparison of 22 identified critical success factors (CSFs) documented by 41 construction experts of various construction projects in Cambodia. The research findings revealed that the most critical factors for contractor’s success are: complexity of a project; social/cultural environment; ability to make timely decision; client confidence in construction team; contractor’s cash flow; client influence; project size; site management; contractor’s experience; and project planning.
Keywords: Construction industry; Critical Success Factors; Analytical Hierarchy Process; Cambodia